10th Anniversary of Cells-Advances in Plant, Algae and Fungi Cell Biology - Allakhverdiev, Suleyman (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Explore a decade of groundbreaking research in "10th Anniversary of Cells-Advances in Plant, Algae, and Fungi Cell Biology." This reprint offers a comprehensive journey into the realms of plant, algae, and fungi cell biology. Delve into the world of genomics, cellular defense mechanisms, mycorrhizal fungi, and the physiology of extremophile algae. A celebration of scientific excellence, this reprint is a valuable resource for researchers, educators, and enthusiasts passionate about these fascinating domains. Join us in commemorating a decade of discovery and advancement in cellular biology.